Managerialism and large-scale assessment: new modes of regulation of basic education - Maria de Fátima Cóssio; Antônio Cardoso Oliveira; Aisllan Augusto Souza (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
This work is an effort of systematisation of the discussions undertaken in Advancing Educational Policy Seminar II PPGE/FaE/UFPel and aims at analyzing the intensification of evaluative mechanisms in the scenario of Brazilian basic education defending the thesis that is part of the process of reconfiguration of the public administration within the framework of the capitalist project and yours consequent changes in the role of the State to cope with the crises and breed new forms of regulation. Use the theorizing of Alfonso (2009), Ball (2004, 2005, 2011), Maroy (2011), Theodore (2011), in the understanding of new public management and adjustment modes, as well as the official and legal documents supporting the understanding of new public management and adjustment modes current policy. Analyzes the public management model assumed by central Governments since the mid 1990 identifing the Managerialism, considering the adoption of business principles and mechanisms of control and accountability within the public machine. Educational policies in force are currently grounded by induction to the improvement of quality indicators, measured through national exams combined to school censuses which result in basic education development index-IDEB. It is believed that the panacea of the evaluation reflects the Organization of systems, of schools and of the classroom, with implications in the curriculum, teaching and training work of students.